THE USE OF PROJECT BASED LEARNING METHOD TO IMPROVE STUDENTS' SKILL IN WRITING DESCRIPTIVE TEXTS TO THE ELEVENTH GRADE STUDENTS OF SMA SWASTA SANTA MARIA KABANJAHE IN THE ACADEMIC YEAR OF 2020/2021 - Barus, Yosephin Kristina; Sari, Anna Stasya Prima; Tarigan, Karisma E. (Kairos English Language Teaching Journal, 2021)
This research was primarily carried out to prove that Project Based Learning (henceforth, PBL) method is effective to improve the students’ skill in writing descriptive texts and to describe the students’ responses towards the learning teaching processes of writing descriptive texts through the use of PBL method. This is Classroom Action Research (henceforth, CAR) which consisted of two cycles. Each cycle consisted of three meeting, excluded pre-test and post-test. There are seven classes in the eleventh grade of SMA Swasta Santa Maria Kabanjahe. There are 36 students in the XI IPA 4 as the research subjects. The analysis of quantitative data showed the improvement of students’ skill in writing descriptive texts. It was shown by the mean score of the pre-test (49,69), the formative test (74,22) and the post-test (82,33). The percentage of the students’ score increased from pre-test to post-test (65,68%). The responses of students can be seen from the total percentage of questionnaires strongly agree about 46,75% and followed by the highest percentage agree about 50,92%. It is advisable that English teachers apply PBL method as a method in order to improve their students’ writing skill.